PWE-108 Toxin A-specific antigen-activated and memory B cells in the circulation of patients with Clostridium difficile infection. (28th May 2012) - Monaghan, T M; Robins, A; Sewell, H F; Mahida, Y R
Abstract : Introduction: In Clostridium difficile infection, antibody-mediated immune response to secreted toxins A and B (which are also the main virulence factors) appears to be important in determining the nature of clinical disease. During a bacterial infection, activation of B cells leads to loss of immunoglobulin (Ig) D and expression of antigen-specific Ig on the cell surface. Following resolution of infection, antigen-specific memory B cells may be detectable in the circulation. Our aim was to identify circulating toxin A-activated B cells during clinical disease and toxin A-specific memory B cells following resolution of C difficile infection. Methods: Purified C difficile toxin A was labelled with Alexa Fluor 488 (toxin A 488 ) and its biological activity and specificity of fluorescence were confirmed using Vero cells and anti-toxin A antibody, respectively. Peripheral blood mononuclear cells (PBMNCs) were obtained from 20 patients [13 female, 7 male; median age 67 yrs (range 32–96 yrs)] with C difficile infection, within 10 days of diarrhoeal onset. For flow cytometry, PBMNCs were incubated on ice in the dark for 1 h in the absence or presence of toxin A 488 . After washing, cells were labelled with anti-CD19-ECD (B cell marker) and anti-IgD-PE (to identify antigen-activated IgD-negativecells). PBMNCs were also polyclonally stimulated in vitro for 6 days to induce differentiation of memory B cells to antibody secreting cells (ASCs). Enzyme-linked immunospot (ELISPOT) assays were used to quantify toxin A-specific IgG ASCs and expressed as percentage of total IgG ASCs. Toxin A-specific IgG antibody levels in sera were studied by ELISA. Data are expressed as median (range). Results: Compared to control buffer, a significantly greater proportion of events (flow cytometry) were seen in the CD19-positive, IgD-negative gate in PBMNCs exposed to toxin A 488 [0.09% (0%–0.54%) vs 0.92% (0.09%–1.78%); p<0.001]. In four patients studied at the same time as flow cytometry, toxin A-specific ASCs were detected by ELISPOT assays (0.04%–2%). In studies over 4 (1–10) months after infection, toxin A-specific ASCs were observed [0.33 (0.07–2.12)%]. Serum anti-toxin A antibodies were detectable in eight patients at the time of clinical disease and in four patients, the antibody levels increased over the following 6 (2–10) months. Conclusion: (1) A small population of toxin A-specific, antigen-activated B cells can be detected in the circulation soon after C difficile infection. (2) In addition to circulating antibody, toxin A-specific memory B cells can be detected over many months after C difficile infection. (3) Future studies can investigate the relationship between the development of B cell responses to C difficile toxins and the nature of clinical disease. Competing interests: None declared.